PROBLEMS AND REMEDIES ASSOCIATED WITH WATER RESOURCE: HARVESTING AND MANAGEMENT - Chengappa, Reshma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Resource scarcity can exacerbate pre-existing tensions or invite new ones, and water is no exception. Within a decade, water could overshadow oil as a scarce and precious commodity at the centre of conflict and peacemaking. Hence, the then UN Sectary General Boutros Boutros Ghali (Egypt’s Minister of State for foreign affairs in 1985) warned that the next war in the Middle East will be fought over water, not politics.2 Unless the present development paradigm and its associated institutions and policies are reoriented to focus on the neglected ecological and equity dimensions of human development, the environmental crisis will eventually culminate in still more diabolic economic, social, and even, political crises. It is with this kind of diagnosis, sustainable development has been proposed as an alternative development paradigm. Adoption and implementation of the new paradigm of sustainable development , i.e., development that simultaneously ensures ecological security, economic efficiency, and social equity, demands far-reaching changes in two major directions. First, to have an altogether new concept of development rooted in the principles of co-existence and mutual dependence on the one hand, and ethical commitments in man-nature relationships on the other hand.3 Envisioning sustainable development is a strategy to achieve immediate economic gains while maintaining indefinitely the productive potential of the renewable resource base.4 The main focus is on the development, management and utilization of water resources in harmony with environmental conservation and the concept of sustainability.5